(untitled) (Sociologisk Forskning, 1999)
This paper examines how competition within a movement affects the overall growth of the movement’s membership. Using data on the Swedish temperance movement, I test hypotheses from three different theories; the theory of cross pressure, rational choice theory, and organizational ecology. My main finding is that intra-movement competition tends to be beneficial for the movement as a whole: as the number of competing organizations increases, the total membership increases. This finding conform best with rational choice theory that emphasize that competition invigorates a social movement.